(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
Nowadays the usage of innovative technologies in the methodology of teaching foreign language has become increasingly important. This article provides an overview of materials on modern computer technologies released over the past few years. The research methods were descriptive, continuous sampling, statistical analysis. During the study, the main directions were identified, allowing to draw conclusions about the possibilities of using and expediency of using innovative technologies in the process teaching foreign language. A significant increase in the number of publications on the stated topics indicates the prospects for innovative technologies in the classroom in a foreign audience.